2015
DOI: 10.1016/j.jviscsurg.2014.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a score for the early diagnosis of anastomotic leakage following elective colorectal surgery

Abstract: The DULK-score is, at present, the most reliable instrument for early diagnosis of AL after colorectal surgery and should be integrated into risk management health policies aiming to improve the quality of care according to the "failure to rescue" concept.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
2
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 16 publications
0
24
2
3
Order By: Relevance
“…Although the key assessment parameters addressed in EWS were addressed in the reviewed educational programmes, other parameters that have been shown to predict clinical deterioration and adverse outcomes were not accounted for. These include patient age (Churpek, Yuen, Winslow, Hall, & Edelson, ), urinary output (Martin et al., ), emotional state (Bian et al., ), frailty (Romero‐Brufau et al., ), diastolic blood pressure (Christofidis, Hill, Horswill, & Watson, ), pulse pressure index (Churpek et al., ), prior admission to ICU (Churpek et al., ) and pre‐existing comorbidities (Hegarty et al., ; Huggan et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Although the key assessment parameters addressed in EWS were addressed in the reviewed educational programmes, other parameters that have been shown to predict clinical deterioration and adverse outcomes were not accounted for. These include patient age (Churpek, Yuen, Winslow, Hall, & Edelson, ), urinary output (Martin et al., ), emotional state (Bian et al., ), frailty (Romero‐Brufau et al., ), diastolic blood pressure (Christofidis, Hill, Horswill, & Watson, ), pulse pressure index (Churpek et al., ), prior admission to ICU (Churpek et al., ) and pre‐existing comorbidities (Hegarty et al., ; Huggan et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…The importance of placing the MD catheter in close relation to the anastomosis has been debated. Jansson et al investigated the importance of catheter placement in 12 patients undergoing right-sided hemicolectomy [18,19]. Median levels of the L/P ratio varied significantly according to catheter location, with the highest values being recorded adjacent to the anastomosis.…”
Section: Catheter Positionmentioning
confidence: 99%
“…At this study, the median interval between appearance of the initial signs of clinical deterioration i.e. a DULK-score >3 and the confirmation of AL was three days While at the study of Martin G et al, it was more helpful as it permitted diagnosis of anastomotic leak three and half days earlier 18.…”
mentioning
confidence: 64%
“…8 Martin et al, revealed mortality rate of about 17%. 18 Therefore, the principle of this study was not to force surgical intervention but to alert the care-takers of the risk of AL and then to intensify surveillance and prescription of the necessary additional investigations leading to early diagnosis.…”
Section: Discussionmentioning
confidence: 99%